1999
DOI: 10.1159/000018152
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Itraconazole in Diabetic Patients

Abstract: Background: Onychomycosis and dermatomycoses can result in serious complications in patients with underlying chronic diseases such as diabetes. To avoid these complications, these dermatological disorders need to be treated efficiently, for example with the triazole antifungal itraconazole. Itraconazole can inhibit the metabolism of drugs by CYP 3A4 and therefore might affect the efficacy of antidiabetic agents. Objective: To investigate this, we assessed the safety of itraconazole in diabetic patients with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
1
16
1
Order By: Relevance
“…The present study confirmed that ITCZ was able to activate the AMPK pathway to suppress hepatic gluconeogenesis by repressing the expression of PGC-1α, PEPCK and G-6-Pase and promote glucose uptake by increasing the expression of GLUT4 in HepG2 cells. The present study observed that ITCZ was non-cytotoxic to hepatocytes, which was consistent with the results by Verspeelt et al (17). AMPK is a heterotrimeric serine/threonine kinase ubiquitously expressed in mammalian organs, including the liver, and acts as a major cellular energy sensor and a master regulator of metabolic homeostasis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present study confirmed that ITCZ was able to activate the AMPK pathway to suppress hepatic gluconeogenesis by repressing the expression of PGC-1α, PEPCK and G-6-Pase and promote glucose uptake by increasing the expression of GLUT4 in HepG2 cells. The present study observed that ITCZ was non-cytotoxic to hepatocytes, which was consistent with the results by Verspeelt et al (17). AMPK is a heterotrimeric serine/threonine kinase ubiquitously expressed in mammalian organs, including the liver, and acts as a major cellular energy sensor and a master regulator of metabolic homeostasis.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, ITCZ is the only azole anti-fungal that is known to have potent anti-angiogenic and anti-proliferative activities in non-small cell lung cancer and glioblastoma cells (10,11), and has been shown to prolong the overall survival of patients with metastatic pancreatic cancer, ovarian cancer and breast cancer (12)(13)(14)(15). Sano et al (16) reported that ITCZ was capable of reducing the inflammatory degree, mucosal hyperplasia and Candida infection in alloxan-induced diabetic rats (16), while Verspeelt et al (17) reported that ITCZ was safe and efficient against dermatological disorders in diabetic patients. Apart from that, Head et al (18) reported that ITCZ activated the adenosine monosphosphate-activated protein kinase (AMPK) signaling pathway in human umbilical vein cells.…”
Section: Introductionmentioning
confidence: 99%
“…Drug interactions are not expected between itraconazole and antidiabetic therapy, since insulin is not metabolised by CYP enzymes [33]. In addition, there is no evidence to suggest that oral antidiabetic medications are metabolised by the same CYP subfamily as itraconazole.…”
Section: Drug Interactions Involving Oral Antifungal Agentsmentioning
confidence: 99%
“…In addition, there is no evidence to suggest that oral antidiabetic medications are metabolised by the same CYP subfamily as itraconazole. For example, tolbutamide is metabolised via the CYP2C9 subfamily [33]. …”
Section: Drug Interactions Involving Oral Antifungal Agentsmentioning
confidence: 99%
See 1 more Smart Citation